Efficient Location of Production in a Simple Neo-Classical Model of General Equilibrium - John M. Hartwick (Queen's University, Department of Economics, 1971)
The theory of the location of the firm is characterized by a number of classic analyses. Each analysis has been concerned with developing a particular property of equilibrium location of the firm, in general, for quite different models of markets. However, there is a consistent conceptual refocusing over time as we move from Weber's analysis in 1919 through Hoover's and Isard's to Moses's in 1958. The purpose of this article is to indicate a basic equilibrium condition for the efficient location of a production process characterized by a neoclassical technology. Producers will locate at sites which maximize profits in the face of existing commodity and factor prices, and transportation costs. This condition was first presented by Moses, geometrically, in a partial equilibrium model. We shall conduct the analysis in a Weber-like model of general equilibrium with a neo-classical technology. In section 2, the model is developed in a context when all markets are geographically distinct and fixed in space. In section 3, the location of producers is treated as a variable.
Keywords: 330